Genotypic and Phenotypic Detection of Mutant Thrombolytic Enzyme (staphylococcal fibrinolysin) Expressed by Mutant Staphylococcus aureus Vancomycin Sensitive S.aureus (VSSA) and Methicillin Sensitive S.aureus (MSSA) by Hydroxylamine Chemical Mutagen - Nebras Rada Mohammed (Journal of Global Pharma Technology, 2019)
The aim of this study in order to determine mutagenesis of virulence S.aureus MRSA, VRSA then make it non virulent VSSA, MSSA by Hydroxylamine (HA) chemical mutagen. The study design of cases are Cross-sectional study so as to  limit types of epidemiologic studies including descriptive study of 500 isolates collected  from different sources of human infections from Tonsils, Nose, Tumors, Urine, Blood and Skin(Acne), all identification by Vitek2-GP. The  antimicrobial sensitivity test done of all 500 isolates against 14 antibiotics, the resistance of antibiotics including Vancomycin 475(95%), Methicillin 500(100%), Imipenem 475(95%), Erythromycin 175(35%), Cloxacillin 225(45%), Azithromycin 275(55%), Ceftazidine 125(25%), Ceftriaxone 75(15%), Cephalexin 75(15%), Norfloxacin 50(10%), Cefoxitin 25(5%), Gentamycin 25(5%), Oxacillin 25 (5%) and Clindamycin25 (5%)  compared with CLSI(2013).The expression of fibrinolytic enzyme (Staphylokinase) done on plasma agar plate to locate hydrolysis around well of plasma on medium, the result showed 180 (69%) isolates of Vancomycin resistance S.aureus (VRSA) and Methicillin resistance S.aureus (MRSA) produces Staphylokinase. The chemical mutagenesis was done by exposure VRSA S.aureus  and MRSA S.aureus  to different doses of chemical mutagen including Hydroxylamine(HA).The study of antibiotics after chemical mutagenesis accomplished on Muller Hinton Agar plate and in vitro to human serum to Vancomycin , Methicillin that have high resistance before mutagenesis, the result showed after chemical mutagenesis by Hydroxylamine (HA) of S.aureus (VRSA) and S.aureus (MRSA) become  sensitive to Vancomycin called Vancomycin Sensitive S.aureus (VSSA) and  sensitive to Methicillin called Methicilline Sensitive S.aureus  (MSSA) with possess higher productivity of Staphylokinase (thrombolytic enzyme).The genetic analysis of sak gene of mutant VSSA, MSSA S.aureus done by genotypic PCR after DNA extraction with  amplification of mutant VSSA, MSSA S.aureus sak gene to determine each isolates possess sak gene of VSSA ,MSSA  S. aureus   with high expression  of staphylokinase, the results showed all isolates of mutant VSSA MSSA S.aureus possess sak gene with 420bp compared with DNA Ladder Marker.  Key words: Fibrinolytic enzyme, Mutagenesis, Mutagenic specificity.